Analisis pembelajaran berdiferensiasi dalam pembelajaran ipas kelas iv topik energi sekolah dasar - Nanda, Putri; Rintayati, Peduk (Didaktika Dwija Indria, 2026)
This study aims to describe the application of differentiated learning in the subject of science and science on the topic of energy in grade IV of SD Negeri Kawatan in the 2024/2025 academic year. Differentiated learning is a form of approach that adapts teaching methods to the interests, needs, and learning styles of students. The research conducted uses a qualitative approach to the case study method. Data were collected through document studies, observations, and interviews which were then analyzed using the interactive analysis model of Miless and Huberman. The results of the study showed that differentiated learning was implemented through three stages, namely: (1) planning, which includes mapping student learning needs through cognitive and non-cognitive diagnostic assessments and compiling teaching tools; (2) implementation, which includes differentiation in content, process, product, and learning environment with learning strategies that vary according to student characteristics; and (3) evaluation, which uses formative and summative assessments to monitor student learning progress and adjust learning strategies. This study concludes that differentiated learning plays an important role in creating inclusive, adaptive, and responsive learning to student diversity.